Nanocomposites composed of HEUR polymer and magnetite iron oxide nanoparticles: Structure and magnetic response of the hydrogel and dried state. (9th March 2015) - Campanella, A.; Di, Z.; Luchini, A.; Paduano, L.; Klapper, A.; Herlitschke, M.; Petracic, O.; Appavou, M.S.; Müller-Buschbaum, P.; Frielinghaus, H.; Richter, D.
Abstract: A novel nanocomposite system composed of hydrophobically modified ethoxylated urethane (so-called HEUR) polymer, which is a telechelic polymer, and coated magnetite (Fe3 O4 ) nanoparticles (MNp) is investigated. Two different kinds of nanoparticle coatings, are used: a hydrophobic coating composed of oleic acid and oleylamine and a hydrophilic coating having the cationic surfactant C18 TAB as an additional layer to the hydrophobic nanoparticles. The structure of the nanocomposites as hydrogels with either MNp separately is analyzed using small angle neutron scattering (SANS). Furthermore, the dried state is studied in complementary SANS experiments. The magnetic response of the dried state is characterized by magnometry observing a superparamagnetic behavior. Graphical abstract: Highlights: A novel nanocomposite formulation based on HEUR polymer and hydrophilic and hydrophobic magnetic nanoparticles is proposed. The hydrophobic nanoparticles interact more strongly than the hydrophilic ones with the polymer network. The increase of the nanoparticles loading does not affect dramatically the dried state structure. High superparamagnetic response is observed for the nanocomposite in the dried state.